Electronic, VR & Augmented Reality Games for Intervention in ADHD - Doulou, Aikaterini; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
In recent years, there has been an increase in the incidence of ADHD in children and adolescents. Many learning and behavioral problems are associated with this disorder as a result of difficulties in cognitive and metacognitive functions. According to Drigas et al. (2021), only when individuals develop these functions can they be integrated in the social environment. Skills such as self-awareness, self-regulation and self-control through inner attention can help children develop alternative strategies to manage their cognitive deficits and adapt in many different environments. With the rapid development of science, several medical and psychological methods have been proposed for the treatment of ADHD, which have contributed significantly to the control of symptoms. In the present work, alternative forms of intervention are investigated, such as video games, with virtual or augmented reality environments that aim to improve the quality of life of these children.